Prevod - literarnozgodovinska stalnica in spremenljivka - Stanovnik, Majda (Primerjalna književnost, 2012)
Slovenian literary translation is strongly developed and in constant interaction with domestic literary production. Literary history partly takes translation into account for pragmatic reasons, but at the same time it also selectively takes into account the premise about its categorical non-originality without expressing a direct opinion about this non-originality.
Keywords: Dolinar, Darko, 1942-; Kos, Janko, 1931-; Kmecl, Matjaž, 1934-; teorija prevajanja; literarni prevod; nacionalna literarna zgodovina; prevodi v slovenščino; arbitrarnost; originalnost; komplementarnost